CCN1 Promotes VEGF Production in Osteoblasts and Induces Endothelial Progenitor Cell Angiogenesis by Inhibiting miR‐126 Expression in Rheumatoid Arthritis. (7th September 2016) - Chen, Cheng‐Yu; Su, Chen‐Ming; Hsu, Chin‐Jung; Huang, Chien‐Chung; Wang, Shih‐Wei; Liu, Shih‐Chia; Chen, Wei‐Cheng; Fuh, Lih‐Jyh; Tang, Chih‐Hsin
ABSTRACT: Angiogenesis is the formation of new capillaries from preexisting vasculature. The perpetuation of angiogenesis plays a critical role in the pathogenesis of various disease states including rheumatoid arthritis (RA). Cysteine‐rich 61 (Cyr61 or CCN1) is an important proinflammatory cytokine in RA. Here, we investigated the role of CCN1 in angiogenesis associated with vascular endothelial growth factor (VEGF) production and osteoblasts. We found higher expression of CCN1 and VEGF in synovial fluid from RA patients compared with healthy controls. CCN1 induced VEGF expression in osteoblasts and increased endothelial progenitor cells (EPCs) angiogenesis by inhibiting miR‐126 via the protein kinase C‐alpha (PKC‐α) signaling pathway. CCN1 knockdown inhibited angiogenesis in both in vitro and in vivo models. Inhibition of CCN1 expression with lentiviral vectors expressing short hairpin RNA (shRNA) ameliorated articular swelling, cartilage erosion, and angiogenesis in the ankle joint of mice with collagen‐induced arthritis (CIA). Our study is the first to describe how CCN1 promotes VEGF expression in osteoblasts and increased EPCs angiogenesis in RA disease. CCN1 may serve as a potential target for RA treatment. © 2016 American Society for Bone and Mineral Research.